Dal Lidar ai 3D City Model: un report ragionato dall'ultimo forum ELMF (GEOmedia, 2010)
A report from the European LiDAR Mapping ForumNavigating virtual cities will be a simple way to explore and understand places situated far from our daily experience. In this context, 3D technology has been indicated as the most important way to interact with a virtual representation of reality as well as a possible evolution for cadastral tools and for services like Google Earth. LiDAR technology is commonly recognized as a main address in this evolution and the ELMF conference, that took place in Den Haag (NL), brought back some interesting point of views related to these new scenarios.